Parad or Butchery of Wild Life in Bastar - Sharma, D. G. (Indian Forester, 1958)
The article describes "parad" - the festival of ruthless destructions and massacre of wild animals by the local adivasis as a matter of right in Bastar Forest Divisions of Madhya Pradesh and suggests measures to change the pattern of celebration of this festival.